Policy analysis in Albanian agriculture using a sector model - Mergos G.; Karadeloglou P.; Stoforos C. (Selected readings on economies in transition, 2000)
Studying the agricultural price policy system under transition to market has merit from a theoretical, as well as a policy, point of view. The APAS (Agricultural Policy Analysis Simulator) model was developed for the agricultural sector of Albania. Three different policy simulations related with both the evolution of income and with prices were constructed. The simulation results of the model showed that the impacts of some policy options that can be introduced in the Albanian economy will probably impose important changes on production, consumption and on the self-sufficiency of the country.